The thermally-driven rotating annulus: horizontal velocities in regular and weakly chaotic flow regimes - Früh, W; Smith, D; Risch, S (University of Oxford, 2015)
The dataset is documented in readme.pdf. The data files are in uncompressed .tar format. This dataset contains 11 1/2 hours of horizontal velocity measurements from four experiments using AOPP's 'small annulus' thermally-driven rotating annulus laboratory experiment. The experiments cover regular (2S, 3AV) and weakly chaotic (3SV) flow regimes. The apparatus consists of two concentric right circular cylinders with height 14.0cm and radii 2.5cm and 8.0cm, with a 17% glycerol / 83% water mixture (by volume) between them. The outer cylinder is heated and the inner cylinder cooled relative to the working fluid, with a temperature difference of approximately 4K, and the apparatus rotates about the co-incident axis of the two cylinders at rates between 0.75 and 3.1 rad/s. This setup mimics the main effects acting on a planetary atmosphere: gravity, rotation, and a heating gradient between low and high latitudes.